(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study explores the ethical perspectives embedded within English proverbs, analyzing their reflection of societal values and moral principles. Through a comprehensive examination of a diverse corpus of proverbs, the research identifies recurring themes related to honesty, diligence, justice, and social harmony. The findings reveal that English proverbs serve as a repository of collective wisdom, offering insights into the cultural norms and ethical standards of English-speaking communities. By contextualizing these proverbs within their historical and cultural milieu, the study underscores the enduring relevance of traditional moral teachings in contemporary ethical discourse. Furthermore, the analysis highlights the role of proverbs in moral education, illustrating how they encapsulate ethical lessons that guide behavior and decision-making. This research contributes to the broader understanding of how language encapsulates and perpetuates ethical values, emphasizing the importance of proverbs as a medium for the transmission of cultural and moral heritage.